BIOLOGICAL ACTIVITY OF MONOSUBSTITUTED AMIDES OF PHTALIC ACIDS - N. V. Kolotova; A. V. Starkova (Разработка и регистрация лекарственных средств)
Anthelmintic, insecticidal, anticoagulant, hemostatic activities of monosubstituted amides of phthalic acid were investigated. Insecticidal, anthelmintic and antico-agulant activities for investigated monosubstituted amides of phthalic and tetrachlorophthalic acids were not discovered. Amides of tetrachlorophthalic acid are characterized by a hemostatic effect. Hemostatic effect of one compound in 1.5 times exceeds the effect of Etamsylate.